INFEKSI VIRUS EBOLA - Rampengan, Novie H. (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: WHO announced the outbreak of Ebola virus (EBOV) which can manifest as fever, severe diarrhea, and vomiting. In Africa, there are 3 types of Ebola viruses that cause the biggest outbreaks: EBOV, Sudan ebolavirus, and Bundibugyo ebolavirus. The transmission of these viruses to human body is via direct contact with blood, secret,organ, or other body fluid of the infected person. The onset of this transmitted disease after the incubation period is 2 to 21 days. The mortality of Ebola infection is still high in human.Keywords: Ebola, virus, Africa outbreakAbstrak: WHO mengumumkan adanya outbreak dari virus Ebola (EBOV) yang ditandai dengan adanya demam, diare berat, dan muntah. Di Afrika, terdapat 3 jenis virus Ebola yang menyebabkan wabah terbesar, yaitu: EBOV, Sudan ebolavirus, dan Bundibugyo ebolavirus. Transmisi virus Ebola masuk ke dalam tubuh manusia ialah dengan kontak langsung dari darah, sekret tubuh, organ atau cairan tubuh lainnya dari orang yang terinfeksi. Onset dari penyakit ini setelah terjadi inkubasi period adalah 2 sampai 21 hari. Mortalitas dari infeksi virus Ebola masih tinggi pada manusia.Kata kunci: Ebola, virus, wabah di Afrika